Optimisation of ammonium tartrate and glucose concentration for gamma linolenic acid production by Cunninghamella sp. 2A1. - Farhila Muhid,; Abdul Jalil Abdul Kader,; Wan Mohtar Wan Yusoff,; Othman Omar,; Aidil Abdul Hamid, (Universiti Kebangsaan Malaysia, 2010)
The effects of ammonium tartrate and glucose concentration on biomass, lipid and GLA accumulation in Cunninghamella sp. 2A1 were investigated using Response Surface Methodology (RSM). Cultivation was carried out in 250 mL shake flask containing 100 mL of nitrogen limiting medium (with various combinations of concentration of ammonium tartrate (1-3 g/L) and glucose (30-60 g/L) at 30°C and 250 rpm agitation for 120 h. The concentration of both compounds significantly affected the biomass, lipid and GLA yield (p<0.05), with the production of each of them being represented by quadratic models. Higher concentration of ammonium tartrate and glucose (2.99 and 59.33 g/L, respectively) was required for enhanced biomass production whereas low nitrogen content with excess glucose was otherwise favoured for lipid and GLA production. Ammonium tartrate and glucose concentration at 1 and 43 g/L, respectively were estimated by the model and proven to give the highest lipid production and GLA yield of 31.06 % (g/g biomass) and 4.15 ×10-2 (g/g lipid less biomass), respectively.